COUPLED HEAT AND SILICA TRANSPORT ASSOCIATED WITH DIKE INTRUSION INTO SEDIMENTARY ROCK: EFFECTS ON ISOTHERM LOCATION AND PERMEABILITY EVOLUTION - Dutrow B.L.; Travis B.J.; Gable C.W.; Henry D.J. (My University, 2001)
An 11-meter-wide alkalic monchiquite dike recovered from the subsurface of Louisiana has produced a metasomatic aureole in the adjacent interbedded carbonate mudstones and siltstones. The asymmetric contact aureole, which extends nearly 6 m above and 4 m below the intrusion, contains the metamorphic minerals, diopside, pectolite, fluor-apophyllite, fluorite, and garnet. A series of coupled heat and mass transport calculations was undertaken to provide thermal constraints for the aureole, in the absence of robust geothermometric assemblages, and insights into accompanying mass transport associated with the sedimentary rock-dike system.Calculations were completed for systems with homogeneous, anisotropic, and layered permeability, κ. Transport, dissolution, and precipitation of silica were also incorporated into calculations. All systems modeled indicate that the thermal pulse waned in ~3 yr with a return to background temperatures in ~10 yr. Heat and fluid transport produce maximum temperature isotherms that are distinctly different in spatial extent and lateral variability for each numerical system. The homogeneous κ case produced isotherms that pinch and swell vertically above the dike and have large lateral variations, in contrast to the anisotropic κ case that produced a single large plume above the dike. The layered system κ case produced the most spatially extensive thermal aureole, unlike that recorded in the rocks.Addition of dissolved silica to the flow system significantly impacts the calculated transport of heat and fluid, primarily due to density changes that affect upwelling dynamics. Although precipitation and dissolution of SiO2 can affect flow through the feedback to permeability, κ changes were found to be minor for these system conditions. Where κ decreased, flow was refocused into higher κ zones, thus mitigating the κ differences over time. This negative feedback tends to defocus flow and provides a mechanism for lateral migration of plumes. Coupled heat and silica transport produces a complex isotherm geometry surrounding the intrusion due to formation of upwelling and downwelling plumes and lateral translation of plumes, leading to variability in the isotherm pattern that does not reflect the inherent heterogeneity of the initial material properties. Initial heterogeneities in κ are not a prerequisite for the development of a complicated flow and transport pattern. In addition, if isotherms reflect isograds, these calculations demonstrate that isograds may not form uniform structures with isograd boundaries characterized by their distance from the heat source.